Endogenous fluorescence of hemosiderin in endometriosis to improve clinical detection - Andrew G. Cabe (Translational Medicine Communications, 2019)
Abstract Background Endometriosis impacts 6–10% of all reproductive- age women. Studies have shown the more effectively endometriosis is removed, the better the patient outcomes for pain reduction and fertility (2, 3). Hemosiderin, glands, and stroma are the histologic markers of endometriosis; optical coherence tomography (OCT) can identify glands and hemosiderin has a known endogenous fluorescence than can be detected by two-photon microscopy (TPM). The hypothesis was that the identification of optical properties of endometriosis using OCT and TPM combined would improve a surgeon’s ability to diagnose and treat by improving endometriosis detection compared to current standards of visual diagnosis. Methods Forty-one women with clinically suspected endometriosis undergoing laparoscopy were consented. Women were enrolled at two clinical sites: University of Texas Health Science Center, San Antonio and Methodist Healthcare System, San Antonio. The surgeon made a clinical diagnosis of suspected endometriosis as 1) yes present 2) maybe present, and 3) not present (controls) from the peritoneum without suspected disease. One-hundred-twenty biopsies were collected from 27 women with visually suspected endometriosis. All three patient biopsy classes were excised and underwent histologic examination as the gold-standard diagnosis for endometriosis. The samples were imaged ex-vivo for optical markers of endometriosis; OCT for endometrial glands and TPM for hemosiderin. Histologic markers were co-registered with optical properties. Biopsies were embedded in agar to maintain orientation during imaging and histological processing. TPM used the endogenous fluorescence of hemosiderin as a marker. OCT used glands as a marker. Sensitivity, specificity, and positive (PPV) and negative predictive values (NPV) were calculated. Results The main-outcome-measure was the statistical comparison of clinical impression, imaging results, and histologic truth. Glands, stroma and hemosiderin were present in 49, 72 and 86% of endometriosis samples confirmed by histology. Clinical suspicion of endometriosis had 98% sensitivity, 53% specificity, 68% PPV, and 96% NPV. In 31 samples of endometriosis maybe being present, 39% were histologically confirmed. Eighty-eight samples were analyzed using OCT-TPM. OCT-TPM had 93% sensitivity, 100% specificity, 100% PPV, and 93% NPV. Conclusions OCT-TPM is useful in identifying endometriosis’ presence or absence. Evaluation of suspected endometriosis by OCT-TPM improves surgeons’ abilities to diagnose and treat endometriosis.